DECENTRALIZED LEARNING MANAGEMENT SYSTEMS: BLOCKCHAIN APPLICATIONS IN HYBRID EDUCATION GOVERNANCE - Mashuri Mashuri; Suhardiman Suhardiman; Suhaimi bin Agus; Lia Amelia; Amin Zaki (Yayasan Adra Karima Hubbi, 2026)
The integration of blockchain technology into hybrid education has the potential to revolutionize the governance of Learning Management Systems (LMS). Traditional LMS often suffer from centralization, which leads to issues such as data security vulnerabilities, inefficiencies in administrative processes, and lack of transparency. Blockchain’s decentralized and immutable nature offers a promising solution to these challenges. This study explores the application of blockchain technology in decentralized LMS to enhance governance, transparency, and security in hybrid education environments. The primary aim of the research is to assess how blockchain can be used to improve administrative processes such as grading, credential verification, and accreditation in hybrid learning systems. A qualitative case study approach was used, involving interviews with administrators, educators, and technology experts, as well as document analysis from institutions implementing blockchain-based LMS. The findings reveal that blockchain integration significantly improves data security, reduces administrative delays, and fosters greater trust among stakeholders. Institutions with blockchain-based LMS reported faster processing of student records and a more transparent grading system. The study concludes that blockchain offers a transformative approach to hybrid education governance by creating more secure, transparent, and efficient systems.